Pergolakan Mesir: Dari Revolusi ke Transisi Demokrasi - Herdi Sahrasad (Budapest International Research and Critics University, 2014)
The 2011 revolution in Egypt started with marches, demonstrations and civil resistance on January 25. Protesters were inspired by the successful uprising in Tunisia, where demonstrators succeeded in bringing down the govern- ment. People came on to the streets demanding the overthrow of Egyptian President Hosni Mubarak. They complained of poverty, unemployment, corruption and autocratic governance of the president who had ruled the country for 30 years. Demonstrators included Islamic, liberal, anti-capi- talist, nationalist and feminist elements. The Egyptian protesters' grievances focused on legal and political issues, including police brutality, state-of-emergency laws, lack of free elections and freedom of speech, corruption, and economic issues including high un- employment, food-price inflation and low wages.The protesters' primary demands were the end of the Mubarak regime and emergency law, freedom, justice, a responsive non-military government and a voice in managing Egypt's resources. Strikes by labour unions added to the pressure on government officials.